2023
DOI: 10.3390/ani13071152
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Selected Factors on the Nutritional Value of the Milk of Cold-Blooded Mares: The Example of the Sokólski Breed

Abstract: This study assessed the effect of access to pasture, lactation number, and foals’ sex on the nutritional value of milk (79 samples) from nine mares. The following were analysed: content of dry matter, protein, fat, lactose, and ash; percentages of α-lactalbumin (α-La), β-lactoglobulin (β-Lg), serum albumin (SA), immunoglobulins (Ig), lactoferrin (Lf), and lysozyme (Lz) in the total protein; and the fatty acid profile. Mares without access to pastures were shown to produce milk with a higher dry matter content,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Additionally, the content of lysozyme in mare milk is twice that of HBM and promotes recovery from gastric ulcers and upper respiratory infections, as well as healing wounds and postoperative scars. The combination of lysozyme and lactoferrin in mare milk is also a type of natural anti-infection substance with bactericidal effects ( 5 , 17 , 18 ).…”
Section: Nutritional Ingredients Of Koumissmentioning
confidence: 99%
“…Additionally, the content of lysozyme in mare milk is twice that of HBM and promotes recovery from gastric ulcers and upper respiratory infections, as well as healing wounds and postoperative scars. The combination of lysozyme and lactoferrin in mare milk is also a type of natural anti-infection substance with bactericidal effects ( 5 , 17 , 18 ).…”
Section: Nutritional Ingredients Of Koumissmentioning
confidence: 99%
“…Barreto et al [ 41 ] reported that approximately 30 million people, mainly in Western Europe and Central Asia, consume mare milk. The promotion of and education about the health-promoting properties of mare milk is increasing consumer demand in many countries, including Poland [ 42 ]. This raw material exhibits very high biological activity that results from the presence of lysozyme, lactoferrin, immunoglobulins, and many other bacteriostatic substances [ 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%